1982
DOI: 10.1007/bf01407871
|View full text |Cite
|
Sign up to set email alerts
|

Optimal quadrature algorithms inH p spaces

Abstract: Summary. The problem of finding optimal error quadrature formulas for 1 evaluating ~ f(x)dx, where fEHp and where p> 1, has been investigated in -1 some recent papers (e.g. [1,3,4, 10]).In this paper we study a class of 'almost optimal' quadrature formulas which were introduced by Stenger [8][9][10][11], for computing the integral f(z) dz, feHp(D).Here D is a simply connected domain in the complex plane 112 and w is a conformal map of D onto the unit disc U.The cost of our quadratures to obtain an e-approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The same estimates are reported in [16], [17], together with the claim that the trapezoidal formula is near optimal in H ∞ (D π/2 , ω). However, the estimates are derived rather indirectly by noting the fact that the study on the optimal quadrature in the space…”
Section: Error Estimatessupporting
confidence: 56%
“…The same estimates are reported in [16], [17], together with the claim that the trapezoidal formula is near optimal in H ∞ (D π/2 , ω). However, the estimates are derived rather indirectly by noting the fact that the study on the optimal quadrature in the space…”
Section: Error Estimatessupporting
confidence: 56%
“…Taken together, and while understanding some limitations, we still believe that modeling the crosslinked alginate polymers as rigid rods provides a computationally accessible strategy to approximate properties of the polymer system and derive hydrogel mesh properties. The model also determined cross-linking regions and correspondingly mesh size based on the egg-box model, where the α-l-guluronate (G) residues in the alginate polymer chain adopt a 2 1 helical conformation and the pair of G residues ("binding cavity") surrounds the calcium ions 60 . Previous work has shown that cross-link density significantly increases for alginate hydrogels with more calcium 16,[61][62] or more polymer content 28 .…”
Section: Discussionmentioning
confidence: 99%
“…We use Lemma 3 to conclude that (10) implies (9). Moreover, given (10), we have equivalence of (8) and (11).…”
Section: Finite Complexitymentioning
confidence: 79%
“…Some progress has recently been made in the worst case setting for the approximation and integration problems over R and R d ; see, respectively, Woźniakowski (2000, 2001). See also Sikorski (1982), Traub et al (1983), Curbera (1998Curbera ( , 2000, and Mathé (1998). In the present paper we study complexity of approximating functions f: R + Q R and their integrals over R + =[0, .)…”
Section: Introductionmentioning
confidence: 99%